2013
DOI: 10.4304/jmm.8.4.338-344
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Design of National Dance Based on Realistic 3D Character

Abstract: Great improvement has been achieved in the protection of national dance through multimedia technology. An interactive design approach for national dance based on realistic 3D character is proposed in this paper. This approach comes with three sub steps: Firstly, the realistic face was reconstructed based on a front photo, in this step, the facial feature points of photo are selected interactively; and then, the realistic face was built through texture mapping and fusion based on the standardized face model dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Network coding is a kind of emerging information transmission technology which overall improves the performance of system, and it is showed that network coding increases the amount of information transmitted singly by the network data, so as to reduce the delivery times of the groups and improve the transmission performance of the network data, such as improving the throughput and bandwidth utilization of the network, and balance the network load and so on. The data transmission in this paper is described as the forwarding process of the data group in the network through multiple-hop transmission, while the forwarding process of the data group on a link is described as the network data transmission [1]. Network coding is initially applied in the wired networks.…”
Section: Introductionmentioning
confidence: 99%
“…Network coding is a kind of emerging information transmission technology which overall improves the performance of system, and it is showed that network coding increases the amount of information transmitted singly by the network data, so as to reduce the delivery times of the groups and improve the transmission performance of the network data, such as improving the throughput and bandwidth utilization of the network, and balance the network load and so on. The data transmission in this paper is described as the forwarding process of the data group in the network through multiple-hop transmission, while the forwarding process of the data group on a link is described as the network data transmission [1]. Network coding is initially applied in the wired networks.…”
Section: Introductionmentioning
confidence: 99%
“…All the flows that constitute a complete sub graph can be encoded at the same time. As shown in Figure 2, flow 1 f , 2 f and 3 f constitute a complete sub graph of coding graph G, there is a connection between every two vertices.…”
Section: Network Coding and Gainmentioning
confidence: 99%
“…The data transmission in this paper is described as the forwarding process of the data group in the network through multiple-hop transmission, while the forwarding process of the data group on a link is described as the network data transmission [1]. Network coding is initially applied in the wired networks.…”
Section: Introductionmentioning
confidence: 99%